2017
DOI: 10.18535/ijmsci/v4i11.15
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diets with Various Calcium and Boron Levels in Prelaying Period on Growth, Bone Ash and Subsequent Performance and Shell Quality of Laying Hens

Abstract: This experiment was conducted to determine the effects of diets with three different levels of calcium (% 0.8, 1.6, 3.2) and four different levels of boron (0, 75, 150, 300 mg kg-1) in prelaying period (14-20 weeks) on growth, bone ash and subsequent performance and egg shell quality of laying hens. A total 864 Super Nick pullets at 14 weeks of age were randomly allocated to twelve treatments arranged in a 3x4 factorial design with six replicates of 12 pullets each. Feed and water provided for ad-libitum acces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Prelay CP effect corroborates with Keshavarz (1998) and Babiker et al (2010) findings. Different prelay Ca levels did not change pullet's FC corroborate with Kocbeker et al (2017). Different prelay diets did not change layer's FC.…”
Section: Feed Consumptionsupporting
confidence: 75%
See 2 more Smart Citations
“…Prelay CP effect corroborates with Keshavarz (1998) and Babiker et al (2010) findings. Different prelay Ca levels did not change pullet's FC corroborate with Kocbeker et al (2017). Different prelay diets did not change layer's FC.…”
Section: Feed Consumptionsupporting
confidence: 75%
“…The EP was numerically increased by 6.37% in T5 fed with high nutrient density prelay diet than control (T0) fed with low nutrient density prelay diet. Previous reports about using different levels of Ca (Kocbeker et al, 2017) in pullet's prelay diet did not show beneficial effect on EP. Low-prelay CP (14.0% and 15.4%) diets (Leeson and Summers, 1981) did not have a significant effect on EP, whereas higher prelay CP (18.1%) diet (Joseph et al, 2000) had higher EP.…”
Section: Egg Productionmentioning
confidence: 75%
See 1 more Smart Citation
“…An increase in the Ca content of the prelay diet from 2.5 to 3.8% improved shell quality, in agreement with data of Hurwitz and Bar (1971) and Brooks (1986) in hens fed prelay diets containing 1.3 vs. 4.1% Ca and 1.0 vs. 3.0% Ca, respectively. Similarly, Koçbeker et al (2017) reported an improvement in shell thickness and breaking strength of the eggs from 20 to 42 wk of age, in hens fed from 14 to 20 wk of age a diet with 3.2 vs. 1.6% Ca.…”
Section: Discussionmentioning
confidence: 75%
“…It increased egg weight but it decreased egg thickness compared to the Control group. In another study [25], it was determined that LW decreased in 150 and 300 mg/kg boron addition compared to those fed by the feed with 0 and 75 mg/kg boron in 20weeks old pullets. Similar findings were also found in the study by Waleed and Hayani [15].…”
Section: Discussionmentioning
confidence: 97%